Three-dimensional rotational angiography in diagnosis of chronic thromboembolic pulmonary hypertension - A. Potępa, Michał; Łabyk, Andrzej; Zieliński, Dariusz; Pruszczyk, Piotr; Roik, Marek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
Chronic thromboembolic pulmonary hypertension (CTEPH) is a rare disease resulting from stenosis or obstruction of the pulmonary arteries due to organized thrombus with disruption of blood flow and derivative microvascular remodelling in 4% of survivors of acute pulmonary embolism (PE). Computed tomography (CT) angiography and conventional pulmonary angiography remain the gold standard to confirm the presence of fibrotic thromboembolic lesions in pulmonary arteries [1, 2]. Pulmonary endarterectomy (PEA) remains the treatment of choice for CTEPH, but in recent years, there has been significant progress in the development of alternate treatments for patients deemed non-operable such as balloon pulmonary angioplasty (BPA) or targeted drug therapy. Patient eligibility for PEA or BPA requires multidisciplinary evaluation at a specialized centre [1–4]. However, interpretation difficulties exist for CT imaging, especially at the level of segmental and subsegmental arteries. This is crucial in deeming eligibility for surgery versus percutaneous intervention. Here, we present a case of a 69-year-old man admitted with a high likelihood of CTEPH. The patient did not have significant comorbidities and reported gradual deterioration of exercise tolerance and exertional dyspnoea (World Health Organization functional class II) since having an acute pulmonary embolism episode in 2019, despite receiving long-term warfarin anticoagulant therapy. Echocardiography performed 6 months after the incident revealed signs of right ventricular dysfunction with high suspicion of pulmonary hypertension (tricuspid regurgitation pressure gradient (TRPG) 76 mm Hg, right ventricular systolic pressure (RVSP) 81 mm Hg, tricuspid annular plane systolic excursion (TAPSE) 17, with preserved left ventricle ejection fraction of 60%).